(untitled) (Journal of Nobel Medical College, 2013)
Intestinal parasitosis is highly prevalent among the general population in Nepal. This study aimed to evaluate the distribution of intestinal parasites among patients attending Nobel Medical College Teaching Hospital, Biratnagar, Nepal. A total of 5,524 stool samples examined by direct smear and Formal-Ether concentration technique were reported. The overall prevalence of intestinal parasitic infection was found to be 15.17% (M=15.65% vs F=14.62%). The overall prevalence of intestinal parasitosis was found to be highest among patients aged 5-14 years (20.66%), followed by elderly people aged > 45 years (16.20%) and least among children aged < 5 years (9.09%). Among various parasites detected, the most common was Entamoeba histolytica (44.86%) followed by Giardia lamblia (33.65%), hookworm (10.50%), Ascaris lumbricoides (5.72%), Strongyloides stercoralis (4.77%), Hymenolepis nana (3.34%), Trichuris trichiura (0.95%) and Enterobius vermicularis (0.23%) respectively. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 13-17 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7666